Ketamine's Amelioration of Fear Extinction in Adolescent Male Mice Is Associated with the Activation of the Hippocampal Akt-mTOR-GluA1 Pathway - Emilija Glavonic; Milorad Dragic; Milos Mitic; Minja Aleksic; Iva Lukic; Sanja Ivkovic; Miroslav Adzic (MDPI AG, 2024)
Fear-related disorders, including post-traumatic stress disorder (PTSD), and anxiety disorders are pervasive psychiatric conditions marked by persistent fear, stemming from its dysregulated acquisition and extinction. The primary treatment for these disorders, exposure therapy (ET), relies heavily on fear extinction (FE) principles. Adolescence, a vulnerable period for developing psychiatric disorders, is characterized by neurobiological changes in the fear circuitry, leading to impaired FE and increased susceptibility to relapse following ET. Ketamine, known for relieving anxiety and reducing PTSD symptoms, influences fear-related learning processes and synaptic plasticity across the fear circuitry. Our study aimed to investigate the effects of ketamine (10 mg/kg) on FE in adolescent male C57 BL/6 mice at the behavioral and molecular levels. We analyzed the protein and gene expression of synaptic plasticity markers in the hippocampus (HPC) and prefrontal cortex (PFC) and sought to identify neural correlates associated with ketamine's effects on adolescent extinction learning. Ketamine ameliorated FE in the adolescent males, likely affecting the consolidation and/or recall of extinction memory. Ketamine also increased the Akt and mTOR activity and the GluA1 and GluN2A levels in the HPC and upregulated BDNF exon IV mRNA expression in the HPC and PFC of the fear-extinguished mice. Furthermore, ketamine increased the c-Fos expression in specific brain regions, including the ventral HPC (vHPC) and the left infralimbic ventromedial PFC (IL vmPFC). Providing a comprehensive exploration of ketamine's mechanisms in adolescent FE, our study suggests that ketamine's effects on FE in adolescent males are associated with the activation of hippocampal Akt-mTOR-GluA1 signaling, with the vHPC and the left IL vmPFC as the proposed neural correlates.